Promoting Cardiac Regeneration and Repair Using Acellular Biomaterials - Vasanthan, Vishnu; Fatehi Hassanabad, Ali; Pattar, Simranjit; Niklewski, Paul; Wagner, Karl; Fedak, Paul W. M. (Frontiers in Bioengineering and Biotechnology, 2020)
Abstract Ischemic heart disease is a common cause of end-stage heart failure and has persisted as one of the main causes of end stage heart failure requiring transplantation. Maladaptive myocardial remodeling due to ischemic injury involves multiple cell types and physiologic mechanisms. Pathogenic post-infarct remodeling involves collagen deposition, chamber dilatation and ventricular dysfunction. There have been significant improvements in medication and revascularization strategies. However, despite medical optimization and opportunities to restore blood flow, physicians lack therapies that directly access and manipulate the heart to promote healthy post-infarct myocardial remodeling. Pathogenic post-infarct remodeling involves collagen deposition, chamber dilatation and ventricular dysfunction. Strategies are now arising that use bioactive materials to promote cardiac regeneration with the intention to attenuate pathologic remodeling by promoting angiogenesis and inhibiting cardiac fibrosis; and many of . Many of these strategies leverage the unique advantage of cardiac surgery to directly visualize and manipulate the heart. Although cellular-based strategies are emerging, multiple barriers exist for clinical translation. Acellular materials have also demonstrated preclinical therapeutic potential to promote angiogenesis and attenuate fibrosis and may be able to surmount these translational barriers. Within this review we outline various acellular biomaterials and, we define epicardial infarct repair and intramyocardial injection, which focus on administering bioactive materials to the cardiac epicardium and myocardium respectively to promote cardiac regeneration. In conjunction with optimized medical therapy and revascularization, these techniques show promise to upregulate pathways of cardiac regeneration to preserve heart function.